Methicillin-Resistance Staphylococcus Aureus (MRSA) in Hospitals: The Unwanted Guest (Medico Legal Update, 2021)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most frequent causes ofNosocomial infections around the world.Aims: This study aimed to detect some diagnostic genes and some virulence factor genes for MRSA isolates.Method: During the period of from August to December 2019, 46 MRSA were isolated from differentclinical samples such as Urinary Tract Infections (UTIs), Wounds infection’s, Diabetics foot patients, Burnpatients and Otitis media in Al- Hussain Teaching Hospital in Thi-qar province, Iraq. All MRSA isolateswere subjected to conventional Polymerase Chain Reaction to detect 16SrRNA and mecA genes and somevirulence factors genes hla and tst-1 genes. Six PCR product were selected and subjected to partial DNAsequencing for the 16SrRNA gene to follow up their possible relationship between them and what recordedglobally in Genbank.Results: The results revealed that all isolates 46(100%) have 16SrRNA, mecA, and hla genes, While only23 isolated (50%) have tst-1 gene. The six PCR product of 16SrRNA was registered in Genbank underofficial accession numbers of (MT605393.1, MT605385.1, MT605394.1, MT605386.1, MT605387.1, andMT605388.1). The phylogenetic tree that was constructed by MEGA10 software showed that there weredifferent molecular relationships among the local Staph. aureus isolates with analogous ones around theworld.